2020
DOI: 10.3390/molecules25071486
|View full text |Cite
|
Sign up to set email alerts
|

Serjanic Acid Improves Immunometabolic Markers in a Diet-Induced Obesity Mouse Model

Abstract: Plant extracts from Cecropia genus have been used by Latin-American traditional medicine to treat metabolic disorders and diabetes. Previous reports have shown that roots of Cecropia telenitida that contains serjanic acid as one of the most prominent and representative pentacyclic triterpenes. The study aimed to isolate serjanic acid and evaluate its effect in a prediabetic murine model by oral administration. A semi-pilot scale extraction was established and serjanic acid purification was followed using direc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 68 publications
0
3
0
1
Order By: Relevance
“…Preclinical evaluations of these molecules suggest that they exert positive effects on metabolic and vascular diseases where inflammation plays a pivotal role 4 . Our group has been focusing on the Cecropia genus due to its high levels of oleanane and ursane pentacyclic triterpenes (PTs), which are associated with the modulation of type 2 diabetes 5–7 . Despite the use of Cecropia herbal products in folk medicine, no reference material is available, which hinders quality evaluation.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Preclinical evaluations of these molecules suggest that they exert positive effects on metabolic and vascular diseases where inflammation plays a pivotal role 4 . Our group has been focusing on the Cecropia genus due to its high levels of oleanane and ursane pentacyclic triterpenes (PTs), which are associated with the modulation of type 2 diabetes 5–7 . Despite the use of Cecropia herbal products in folk medicine, no reference material is available, which hinders quality evaluation.…”
Section: Introductionmentioning
confidence: 99%
“…4 Our group has been focusing on the Cecropia genus due to its high levels of oleanane and ursane pentacyclic triterpenes (PTs), which are associated with the modulation of type 2 diabetes. [5][6][7] Despite the use of Cecropia herbal products in folk medicine, no reference material is available, which hinders quality evaluation.…”
mentioning
confidence: 99%
“…La AMPK es un heterotrímero (con subunidades α, β y γ) que realiza una importante función regulando el metabolismo celular y produciendo un balance entre el suministro de nutrientes y la demanda de energía 7,8 . El incremento en la proporción AMP/ATP o ADP/ATP induce la activación de AMPK que desencadena una ruta de señalización que involucra la fosforilación de numerosas enzimas metabólicas,…”
Section: Introductionunclassified
“…The PTs mentioned above feature a common structural scaffold—an oleanyl and ursanyl—reported to modulate some human and animal metabolic pathways. For instance, the proven gene expression inhibition of proinflammatory cytokines by serjanic acid is crucial to prevent or ameliorate pancreatic β-cell damage within a diabetic state, as shown in a preclinical murine model [ 7 ]. Various experimental models have demonstrated that islet inflammation plays a significant role in the pathogenesis of β-cell failure patients.…”
Section: Introductionmentioning
confidence: 99%